The capsular ligaments provide more hip rotational restraint than the acetabular labrum and the ligamentum teres: an experimental study - van Arkel, R. J. (Bone Joint J, 2015)
In this in vitro study of the hip joint we examined which soft tissues act as primary and secondary passive rotational restraints when the hip joint is functionally loaded. A total of nine cadaveric left hips were mounted in a testing rig that allowed the application of forces, torques and rotations in all six degrees of freedom. The hip was rotated throughout a complete range of movement (ROM) and the contributions of the iliofemoral (medial and lateral arms), pubofemoral and ischiofemoral ligaments and the ligamentum teres to rotational restraint was determined by resecting a ligament and measuring the reduced torque required to achieve the same angular position as before resection. The contribution from the acetabular labrum was also measured. Each of the capsular ligaments acted as the primary hip rotation restraint somewhere within the complete ROM, and the ligamentum teres acted as a secondary restraint in high flexion, adduction and external rotation. The iliofemoral lateral arm and the ischiofemoral ligaments were primary restraints in two-thirds of the positions tested. Appreciation of the importance of these structures in preventing excessive hip rotation and subsequent impingement/instability may be relevant for surgeons undertaking both hip joint preserving surgery and hip arthroplasty. Cite this article: Bone Joint J 2015; 97-B:484–91.